Cystic Fibrosis-A Joujou for Pathogens - Karthikeyan, C.; Ramanathan, N.; Adline Princy, S. (Asian Journal of Chemistry, 2010)
Single nucleotide polymorphism (SNP) is a variation occurring in the single nucleotide of the genome. It is more precise to call it a point mutation. A single nucleotide polymorphism occurring in the CFTR gene causes cystic fibrosis. It includes the upset of Cl– ion transport that in turn results in the absorption of Na+ ions by the cells of the respiratory tree. This absorption later happens to be the initiating factor for various pathogens to breed in the respiratory tract with the sticky mucus as a supporting medium. The various pathogens include Pseudomonas aeruginosa, Staphylococcus aureus, Pseudomonas cepacia etc. These pathogens communicate among themselves in a complicated way and organize into micro colonies so that they are able to pose an effective threat to the human defense mechanisms. This inter communication among pathogens is made possible by a complex and sensitive mechanism known as "Quorum Sensing" which involves micro molecules called "autoinducers". As a result of quorum sensing, the gene expressions within the pathogens are altered which enable the pathogen to diversify their virulence expression. The diversification of virulence factors leads to various hardships in the process of drug designing and targeting. Moreover several antimicrobial therapy and prophylaxis have been discovered in the past so as to safeguard the human race from the jaws of cystic fibrosis but all in vain. Present study focuses towards the proposal of an effective idea for this biological problem. This could be possible by making the concepts of chemistry join hands with bio-informatics so that a novel technique called "Chem-informatics" emerges. It is rather optimistic to trust on this emerging methodology so that something useful to the mankind may be contributed in the near future not only for cystic fibrosis but also for the rest of the diseases that swivel around the Homo sapiens.